Diagnóstico sobre el grado de asimilación de los contenidos históricos en Educación Básica y universitaria el caso de Riobamba, Ecuador del 2016 - Berrones Yaulema, Laura Pilar (2018)
Throughout the history of Ecuador several reforms have been made to the educational curriculum, trying to find the most appropriate methodology, so that students assimilate the information correctly, at the beginning prevailed behavioral and inoperative paradigms that became monotonous and repetitive, as the very little time has been the difference. This research project proposes: this exam was approved by the application of a questionnaire for its subsequent analysis and interpretation of the methodology used to determine the quantitative nature, aimed at students of Basic General Education (10th year), and the entire population university (UNACH of Ciencias de la Education Humanas y Tecnologias Faculty, for this was the fieldwork, that is, the direct contact with the students of the institutions. It is necessary to emphasize the importance of this research project, since the competitive real world demands quality in education. With the results after the data collection and analysis, it was concluded that due to the low level of knowledge that the students assimilated, the techniques and methods used by the teachers have been inefficient, we suggest the creation of an innovative methodology, in order to change the actual situation, since as future teachers of this branch, we must strengthen the gaps that students have to allow the proper teaching-learning process.